MANAJEMEN UNIT USAHA PONDOK PESANTREN BADRIDDUJA - Siti Aisyah; Fasihul lisan; Muhammad Rofek (IZZI: Jurnal Ekonomi Islam, 2022)
Islamic boarding school is one of the institutions that maintains the traditional culture of the Indonesian people, especially in the field of religion and noble character as well as the preservation of Indonesian traditional culture to face the development of modernization in people's lives. The purpose of this study is to find out how the management of Hamdalah's business unit in developing its business. qualitative research method with a case study research approach to describe the objectives of the management research of the Hamdalah Islamic Boarding School Badridduja Kraksaan Probolinggo. The research was conducted by conducting interviews (interviews), and observations. In terms of data sources, additional materials originating from written sources can be divided into sources of scientific books and magazines, sources from archives, personal documents, and official documents. From the results of the interview above, it can be seen that the initial capital from the Hamdalah business unit was 20,000,000 where the money came from loan funds to the Badridduja Islamic boarding school then the capital debt to the Islamic boarding school was repaid using a credit system, while for the time period for the repayment of the capital debt, the Hamdalah business unit paid it off. within 2 years. The Hamdalah business unit, the Badridduja Islamic Boarding School, was established in 2019 and Nyai Zumroh is the leader. Human resource management applied in the management of the Hamdalah business unit is to divide tasks and time with the hope that employees can work optimally and Nyai Zunroh as a leader always takes personal approaches and is open to subordinates, always providing direction to subordinates.